Arab water security problems and the potential for creating a unified Arab strategy.: Arab water security problems and the potential for creating a unified Arab strategy. (jornal of the libyan geographical society, 1997)
What is Arab water security?In our view, Arab water security means understanding the reality of Arab water resources in terms of their reserves, the diversity of their sources, methods of investing in them, how to improve their quality, and ensuring their availability in a quantity that meets the needs of human consumption, sufficient agricultural production, industrial growth, and structural balance. Thus, it can be said that the concept of water security has become synonymous with the concept of Arab national security.This study will focus on water resources in terms of their volume and diversity. Freshwater resources in the Arab world include all surface and groundwater sources, annual rainfall, and freshwater springs on the continental shelf. These sources are classified into two groups: traditional and modern.
Keywords: Water security; Water wealth; Human consumption; The Arab world; Traditional sources; Modern sources